2002
DOI: 10.1046/j.1523-1755.2002.00223.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP increases rat inhibitor of apoptosis protein (RIAP1) mRNA in renal mesangial cells

Abstract: These data establish, to our knowledge for the first time, that RIAP1 mRNA levels are regulated by the cAMP-signaling pathway and suggest potential new avenues of therapy to modulate apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Focal adhesion kinase (FAK) has been shown to activate the phosphatidylinositol 3-kinase (PI3K)/Akt survival pathway and NF-B, resulting in upregulation of c-IAP1, c-IAP2, and XIAP in HL 60 cells (49). NF-B also interacts with the cAMP signaling pathway and regulates transcription of IAP expression through the cAMP-responsive elements that are present in the promoter of IAP genes (9,28).…”
Section: Discussionmentioning
confidence: 99%
“…Focal adhesion kinase (FAK) has been shown to activate the phosphatidylinositol 3-kinase (PI3K)/Akt survival pathway and NF-B, resulting in upregulation of c-IAP1, c-IAP2, and XIAP in HL 60 cells (49). NF-B also interacts with the cAMP signaling pathway and regulates transcription of IAP expression through the cAMP-responsive elements that are present in the promoter of IAP genes (9,28).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from activation of PKC and PI3-kinase, PMA is also an activator of PKA (70). The cAMP/PKA pathway is an alternative pathway of transcriptional regulation of IAP-1 expression and may constitute a powerful protective agent in cells exposed to stress conditions (71). Treatment with the selective PKA inhibitor, H89, did not attenuate the PMA-induced cIAP-2 expression, suggesting that PKA is not FIG.…”
Section: Ciap-2 Regulation In Human Colon Cancersmentioning
confidence: 98%
“…cAMP regulates numerous cellular processes, including gene expression, cell differentiation, cell cycle progression and apoptosis, both in a PKA-dependent and PKA-independent manner [17-19]. Some studies indicate that analogues of cyclic nucleotides cause apoptosis in renal mesangial cells, multiple myeloma cells and human cancer cell-sandactivation of cAMP signaling enhances Fas-mediated apoptosis and activation-induced cell death through potentiation of caspase-8 activation [20-23]. In contrast, there have also been studies that have shown that cAMP analogues inhibit apoptosis induced by different stimuli in hepatocytes, neutrophils, smooth muscle cells, andpre-B acute lymphoblastic leukemia NALM-6 cells [15,24,25].…”
Section: Introductionmentioning
confidence: 99%